Hubungan Pola Asuh Ibu Bekerja terhadap Kemandirian Anak Usia 5-6 Tahun di TK - Roudlotun Ni’mah; Farida Isroani (Multiverse: Open Multidisciplinary Journal, 2022)
Independence is one of the important traits for early childhood to have. One of the factors that influence children's independence is parenting style. The type of parenting style of parents will determine how independent a child is formed. This study aims to reveal the relationship between parenting patterns of working mothers and the independence of children aged 5-6 years with the formulation of the problem: 1) working mothers parenting, 2) independence of children aged 5-6 years in Al-Hidayah Kindergarten. Maibit, and 3) the relationship between working mothers' parenting patterns on the independence of children aged 5-6 years. This research belongs to the type of quantitative research with statistical methodology. The data used are primary and secondary data obtained through the process of extracting data using documentation and questionnaire methods. The data were analyzed by using Product Moment correlation analysis technique. From the results of data analysis, the following conclusions were obtained: 1) The parenting pattern of working mothers for their children strongly trains children's independence, as evidenced by the high percentage of filling out questionnaires on statements about parenting that trains children's independence 2) Independence of children aged 5- 6 years is very good, as evidenced by the results of the questionnaire which shows that on average the children are able to show their independence and 3) There is a relationship between the parenting pattern of working mothers and the independence of children aged 5-6 years. This is evidenced by the results of the calculation of product moment 0.520 which is greater than (r) table both in the 1% and 5% significance level.